2015
DOI: 10.4049/jimmunol.1402448
|View full text |Cite
|
Sign up to set email alerts
|

An NK Cell Population Lacking FcRγ Is Expanded in Chronically Infected HIV Patients

Abstract: We previously demonstrated that NK cells from HIV-infected individuals have elevated expression of activation markers, spontaneously degranulate ex vivo, and decrease expression of a signal-transducing protein for NK-activating receptors, FcRγ. Importantly, these changes were maintained in virologically suppressed (VS) individuals receiving combination antiretroviral therapy (cART). In this study, we show that loss of FcRγ is caused by the expansion of a novel subset of FcRγ−CD56dim NK cells with an altered ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
90
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(103 citation statements)
references
References 55 publications
(46 reference statements)
12
90
0
Order By: Relevance
“…An additional NK cell subset lacking the aNKR FcRy is expanded in chronically HIV-1 infected individuals. Similar to what it has been observed with HCMV-induced NK cells, this latter population expresses low levels of NKp30 and is endowed with remarkably high ADCC activity [47]. Taken together, these data indicate that NK cells from HIV and HCMV co-infected patients have unique immunologic features that can be potentially targeted for developing anti-viral therapeutic approaches.…”
Section: Nk Cells and Hiv-1 Pathogenesissupporting
confidence: 78%
“…An additional NK cell subset lacking the aNKR FcRy is expanded in chronically HIV-1 infected individuals. Similar to what it has been observed with HCMV-induced NK cells, this latter population expresses low levels of NKp30 and is endowed with remarkably high ADCC activity [47]. Taken together, these data indicate that NK cells from HIV and HCMV co-infected patients have unique immunologic features that can be potentially targeted for developing anti-viral therapeutic approaches.…”
Section: Nk Cells and Hiv-1 Pathogenesissupporting
confidence: 78%
“…FcεRIγ- NK cells expanded robustly in vitro when co-cultured with infected cells and plasma containing virus-specific antibodies against both HCMV and influenza [88]. Notably, the frequency of FcεRIγ- NK cells was increased in HIV + individuals and was correlated with HCMV-specific antibody titers in HIV − individuals [89]. Further mechanistic studies are required to address the underlying pathways promoting the generation and expansion of FcsRIγ- NK cells, and whether there is a clinical relevance for these cells in the context of HCMV infection.…”
Section: Antigen-dependent Generation Of Nk Cell Memorymentioning
confidence: 99%
“…Mechanistically this increased activity has been linked to a switch from FcγRIIIa association with FcRγ/CD3-ζ to CD3-ζ alone by loss of FcRγ expression and synergistic signalling from CD2 which acts as a co-receptor for FcγRIIIa (reviewed in [113]). This population of "ADCC-specialised" NK cells has also been identified in viremic and cARTtreated HIV infected patients where it is expanded to comprise 90% of the mature NK compartment [112].…”
Section: Fcγriiia a Key Activating Receptormentioning
confidence: 99%
“…FcγRIIIa is the most abundant FcγR on NK cells which are major mediators of ADCC [16] and signals via the signal transduction subunits FcRγ and/or CD3-ζ [13]. Recent studies of HCMV infection have identified the expansion of adaptive NK cells with altered expression of Syk [111] and down regulation of FcγRIIIa, but which are more potent ADCC effectors and producers of IFNγ [112]. Mechanistically this increased activity has been linked to a switch from FcγRIIIa association with FcRγ/CD3-ζ to CD3-ζ alone by loss of FcRγ expression and synergistic signalling from CD2 which acts as a co-receptor for FcγRIIIa (reviewed in [113]).…”
Section: Fcγriiia a Key Activating Receptormentioning
confidence: 99%